Perbedaan Pengetahuan Pada Pendidikan KesehatanMetode Ceramah Dan Media Leaflet Dengan Metode Ceramah Dan Media Video TentangBahaya Merokok Di SMK Kasatrian Solo - Bachtiar, Muhammad Yusuf, Arina Maliya, S.Kep.,M.Si., Med, Dewi Suryandari, S.Kep., Ns (2015)
Background: Knowledge about the dangers of smoking means everything and all information obtained concern in the matters relate to the dangers of smoking. The use of appropriate methods and media can influence respondents' knowledge. This study aims to determine differences between knowledge of health education lecture and media leaflet with a lecture and video media about the dangers of smoking in SMK Kasatrian Solo. Method: This type of study is a quasi experimental design, pretest-posttest design with two group designs. Samples were students of class 10 major in Computer Network with 30 students, which is then divided into two groups: a group of 15 students with lecture and media leaflet and then 15 students with lecture and video media. The sampling technique uses accidental sampling. Instrument: Instruments of research uses knowledge questionnaires given before and after health education. Research data analysis uses the comparative test, the paired sample test and independent sample test. Results: The results of the research is known by the respondent in both of groups before being given medical education in enough category, after being given medical education about the changing proved with the increasing in good category. Conclusion: 1) There is the influence of health education on knowledge about the dangers of smoking on health education lecture and media leaflets and a lecture and video media; 2) Method of lectures and video media is more influential in the increased knowledge about the dangers of smoking with the difference in value of increased knowledge about 1.2.